2017
DOI: 10.1007/s12192-016-0758-5
|View full text |Cite
|
Sign up to set email alerts
|

The expression of DAMP proteins HSP70 and cancer-testis antigen SPAG9 in peripheral blood of patients with HCC and lung cancer

Abstract: There are different views of how the immune system participates in the reaction to cancer. Here, we evaluated expression of DAMP proteins HSP70 and cancer-testis antigen SPAG9 in patients with hepatocellular carcinoma (HCC) and lung cancer to explore tumor immunity. Our analysis showed that levels of HSP70 and SPAG9 antibody were significantly higher in the serum of lung cancer and HCC patients than in the serum of healthy subjects (P < 0.001), but there were no differences in levels of HSP70 antibody in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…We also detected a high expression of HSP70 and TLR4 in cancer tissues of patients with liver cancer. Our previous study revealed that the serum HSP70 levels in patients with hepatitis cirrhosis, as well as in patients with liver cancer, were higher than normal (19). These findings revealed that DAMP HSP70 is associated with the pathological process both of inflammation and cancer.…”
Section: Discussionmentioning
confidence: 89%
“…We also detected a high expression of HSP70 and TLR4 in cancer tissues of patients with liver cancer. Our previous study revealed that the serum HSP70 levels in patients with hepatitis cirrhosis, as well as in patients with liver cancer, were higher than normal (19). These findings revealed that DAMP HSP70 is associated with the pathological process both of inflammation and cancer.…”
Section: Discussionmentioning
confidence: 89%
“…Elevated serum Hsp70 and Hsp90 have been reported in patients with cachexia-prone cancers including lung 42 47 , colorectal 48 and pancreatic cancer 49 , but not in patients with breast cancer 50 that is not highly prone to cachexia. Importantly, serum Hsp70 and Hsp90 levels in cancer patients increase with the development of pathological grade and clinical stage 43 , 44 , 46 , and the increase correlates with mortality in cancer patients 42 , 48 , to which cachexia is a major determinant.…”
Section: Discussionmentioning
confidence: 99%
“…However, these clinical studies did not examine whether elevation in serum Hsp70/90 and EVs correlated with cachexia. Because at least partially that non-standardized assays were used in these clinical studies, the reported values of basal serum Hsp70 in humans vary from 0.04 49 to 8.5 ng/ml 47 , and basal serum Hsp90α levels vary from 17 50 to 40 ng/ml 43 . The basal serum Hsp70 levels we measured in mice (~3 ng/ml, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also showed humoral response against SPAG9 in various histotypes of ovarian cancer patients. 9 Recently, SPAG9 has also been shown to generate strong humoral response in hepatocellular carcinoma and lung cancer patients, 13 indicating its therapeutic potential as a tumor-specific biomarker for cancer management. In present investigation, our data show that ablation of SPAG9 in ovarian cancer cells resulted in increased DNA damage, cell cycle arrest, apoptosis, reduction in cellular migration and invasion ability in in vitro and reduced ovarian tumor growth in human xenograft mouse model.…”
Section: Discussionmentioning
confidence: 99%